The impact of genetics and environment on the polar fraction metabolome of commercial Brassica napus seeds: a multi-site study. Issue 3 (5th September 2019) - Bennouna, Djawed; Avice, Jean-Christophe; Rosique, Clément; Svilar, Ljubica; Pontet, Célia; Trouverie, Jacques; Fine, Frédéric; Pinochet, Xavier; Fraser, Karl; Martin, Jean-Charles
Abstract: This study was designed to elucidate the biological variation in expression of many metabolites due to environment, genotype, or both, and to investigate the potential utility of metabolomics to supplement compositional analysis for the design of a new resilient cultivar of Brassica napus that can be steady in phytochemicals in different regions in France. Eight rapeseed varieties, grown in eight regions of France, were compared using a non-targeted metabolomics approach. The statistical analysis highlighted the distance and closeness between the samples in terms of both genotypes and geographical regions. A major environmental impact was observed on the polar metabolome, with different trends, depending on the varieties. Some varieties were very sensitive to the environment, while others were quite resilient. The identified secondary metabolites were mapped into the KEGG pathway database to reveal the most sensitive target proteins susceptible to environmental influences. A glucosyl-transferase encoded by the UGT84A1 gene involved in the biosynthesis of phenylpropanoid was identified. This protein could be rate limiting/promoting in this pathway depending on environmental conditions. The metabolomics approach used in this study demonstrated its efficiency to characterize the environmental influence on various cultivars of Brassica napus seeds and may help identify targets for crop improvement.